2023
DOI: 10.1007/s40962-023-01009-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Aluminium AA7075 Hybrid Composite Foams (AHCFs) Using SiC and TiB2 Reinforcement

Abstract: In this study AA7075/SiC/TiB2 closed-cell Aluminium hybrid composite foam (AHCFs) with different densities was fabricated by top-loaded bottom pouring stir casting technique. This technique uses oyster-shell powders (CaCO3 2.5 wt. % of composite with 60 μm size) as blowing agents and no viscosity-enhancing ingredient. The silicon carbide (SiC 0, 3, 6, 9, and 12 wt. % with 25 μm) and titanium di-boride (TiB2 3 wt. % with particle size 15 μm) are used as primary and secondary reinforcement agents. It has been no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In [31], the plastic collapse of an AA7075 alloy foam reinforced with micro-sized SiC and TiB2 is compared with an A356 alloy foam containing micro-sized SiC particles, which are, respectively, 25MPa and 5MPa (Figure 12b). Here, again, it was difficult to analyze the obtained results, because the alloys are different, as are the introduced micro-powders.…”
Section: Pressionmentioning
confidence: 99%
“…In [31], the plastic collapse of an AA7075 alloy foam reinforced with micro-sized SiC and TiB2 is compared with an A356 alloy foam containing micro-sized SiC particles, which are, respectively, 25MPa and 5MPa (Figure 12b). Here, again, it was difficult to analyze the obtained results, because the alloys are different, as are the introduced micro-powders.…”
Section: Pressionmentioning
confidence: 99%
“…The setup's panel incorporates various key components, including a dielectric chamber for mixing, mist flow meter for a dielectric, manual regulators, and pressure gauges that play a crucial role in determining the working pressure of the dielectric medium. After that, the material removal rate is calculated according to Sundriyal s. discussed in literature survey 22,28 .…”
Section: Powder MIX Edmmentioning
confidence: 99%
“…From Figure 9(b), which shows the effect of input parameters on Tool Wear Rate (TWR), it can be seen that a lower value of tool wear rate was observed when the mist of powder concentration increased on duty cycle, the pulse on time, and discharge current increased due to this. The tool's strong thermal conductivity and the workpiece materials low specific heat make for more effective TWR findings 11,28 . It was observed that the lower the tool wear rate in PM-EDM as compared to ND-EDM at input parameters of 4 g/l powder concentration, a pulse From Figure 11(a), which shows the effect of various inputs on surface roughness, it can be seen that when there are increases in discharge current, duty cycle, and pulse on time, a better surface of finish is achieved.…”
Section: Factor-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminium alloys and their composites have a wide range of applications such as automobile structures, aerospace structures, and marine applications [15][16][17][18]. Al 7075-T651 alloy is one of the well-known Armour-grade aluminium alloys [19,20] because of its high strength and low weight properties.…”
Section: Introductionmentioning
confidence: 99%